PENDIDIKAN POLEKSOSBUD DAN IDEOLOGI DALAM MEMBANGUN KARAKTER BANGSA - Bagyo Handoko Sutiksna (Jurnal Ilmiah Econosains, 2012)
Abstract Facing the era of global markets, the world of education is expected to have a curriculum and syllabus that leads to the formation of a specific competence that is accredited and certified nationally and even internationally so as to link and mach with the real needs of business and labor market and not leave the culture of the nation's culture. Education is to contribute in developing human resources (HR) quality, with indicators of qualified experts, skilled, creative, innovative, and have the attitude (attitude and behavior) is positive. Nation's character development education model (building future leaders) is through the development of the values possessed by Indonesian people become content in the curriculum of global markets. Keywords: global markets, nation's culture, link and mach.